ANALISIS DAN IMPLEMENTASI JARINGAN THIN CLIENT MENGGUNAKAN LINUX TERMINAL SERVER PROJECT PADA JARINGAN LAN - Hasibuan, Doli; Larosa, Fati Gratianus Nafiri; Simanjuntak, Rico VA (Universitas Methodist Indonesia, 2019)
The development of computer technology both in software and hardware is very fast. These two aspects are interrelated with each other and cannot be separated. LTSP, Linux Terminal Server Project is a project started by James A McQuillan as a diskless networking project based on the GNU/Linux operating system. Called a diskless network, because the client is not equipped with a hard disk. All application software and operating systems needed by the client computer are served and managed by the server computer. In this design, a laptop with an Intel processor is used as a server and a PC as a client. LTSP will be integrated into the Linux operating system ubuntu 16.04, and as a provider of diskless thin client service platforms is LTSP (Linux Terminal Server Project). With LTSP, the construction of a diskless network is expected to be more efficient. Diskless network technology is one solution that can be applied in dealing with the problem of investing in computer technology hardware with predetermined specifications.